Ultrasound Stimulation Modulates Microglia M1/M2 Polarization and Affects Hippocampal Proteomic Changes in a Mouse Model of Alzheimer's Disease - Xinliang Lu; Wenxian Sun; Li Leng; Yuting Yang; Shuting Gong; Qi Zou; Haijun Niu; Cuibai Wei (Immunity, Inflammation and Disease)
ABSTRACT Background The effectiveness of ultrasound stimulation in treating Alzheimer's disease (AD) has been reported in previous studies, but the underlying mechanisms remain unclear. This study investigated the effects of ultrasound stimulation on the proportion and function of microglia of different phenotypes, as well as on the levels of inflammatory factors. Additionally, it revealed the alterations in proteomic molecules in the mouse hippocampus following ultrasound stimulation treatment, aiming to uncover potential new molecular mechanisms. Methods Ultrasound stimulation was used to stimulate the hippocampus for 30 min per day for 5 days in the ultrasound stimulation‐treated group. Amyloid plaque deposition was measured using immunofluorescence staining. M1 and M2 type microglia were labeled using immunofluorescent double staining, and the ratio was calculated. The levels of Aβ42, IL‐10, and TNF‐α were determined using ELISA kits. The quantitative proteomics method was employed to explore molecular changes in hippocampal proteins. Results Ultrasound stimulation treatment reduced the average fluorescence intensity of amyloid plaques and the concentration of Aβ42. Compared to the AD group, ultrasound stimulation resulted in a 14% reduction in the proportion of M1 microglia and a 12% increase in the proportion of M2 microglia. The concentration of the anti‐inflammatory factor IL‐10 was significantly increased in the ultrasound stimulation‐treated group. Proteomics analysis revealed 753 differentially expressed proteins between the ultrasound stimulation‐treated and AD groups, with most being enriched in the oxidative phosphorylation pathway of mitochondria. Additionally, the activity of cytochrome c oxidase, involved in oxidative phosphorylation, was increased after ultrasound stimulation treatment. Conclusions Ultrasound stimulation affects microglial polarization, reduces amyloid plaque load, and enhances levels of anti‐inflammatory factors in APP/PS1 mice. Proteomics analysis reveals molecular changes in hippocampal proteins after ultrasound stimulation treatment. The mechanism behind ultrasound stimulation‐induced modulation of microglial polarization may be related to changes in mitochondrial oxidative phosphorylation.